Mapping the daily media round: novel methods for understanding families' mobile technology use. Issue 1 (2nd January 2018) - Taylor, Katie Headrick; Takeuchi, Lori; Stevens, Reed
ABSTRACT: The pervasiveness of mobile devices in families' homes has dramatically changed the physical and temporal arrangement of co-viewing media content; the representative image of American families seated around a TV set is an anachronism. But understanding and describing contemporary co-participation arrangements around digital media is challenging because of the mobile nature of these activities. As researchers, our greatest challenge is to observe people's digital media use that is increasingly 'on-the-move' in an effort to understand the significance and possibilities these devices have in family life, learning, and engagement in and across different settings. This article describes an innovative study design for understanding how mobile technologies influence the ways in which families learn together. We analyze the movement of digital media practices, where they are located, and how digital co-participation within families is distributed across time and space.